The use of prosthetic obturators for dental rehabilitation of patients with oral cancer - R. M. Jafarov (LLC "Endo Press", 2023)
The article presents an analytical review of current data on the effectiveness of the use of obturator prostheses in patients with oral cancer after treatment. Literature search was performed on Ovid MEDLINE, Ovid Embase, Web of Science, PubMed, Scopus, Yandex in the period 2012 - 2022. The search terms were head and neck cancer, oral cavity cancer, orthopedic dental rehabilitation, prosthetics, obturator prosthesis. The success of orthopedic rehabilitation with an obturator prosthesis depends on the size and shape of the dentition after surgical removal of the cancer, as well as on the quality of the soft tissues covering the alveolar process and the resection cavity. Obturator prostheses improve oral function in patients with maxillary defects. The growth of 3D technologies in the diagnosis, planning and rehabilitation of the oral cavity is enormous, and it is advisable to use them to build models and prostheses.